The body in the library: An investigative celebration of deviation, hesitation, and lack of closure. Issue 1 (February 2019) - Kociatkiewicz, Jerzy; Kostera, Monika
The unexpected, if still clichéd, discovery of a body in the library introduces Agatha Christie's plot starring the genius amateur detective, elderly Miss Marple. We will use the same situation as the starting point of our article and investigation, promising both the unmasking of the culprit and the departure from the currently standard form of an academic text. In a self-consciously rambling and digressive text, we will touch on various issues relevant to writing what we consider good social science, and the difficulties in doing so. Firmly reaffirming the need for writing organization studies and social science in the narrative mode, we trace what we see as the decline in quality and joyousness of contemporary management journal articles, and attempt to demonstrate, both through narrative means and by more traditional academic reasoning, how and why it is important to embrace variety in the ways knowledge in the social sciences is constructed and communicated.